Scientometric Analysis-based Re of Drought Indices for Assessme and Monitoring of Drought - Mohan, Kamalanandhini (Geographica Pannonica, 2023)
The major cause of a drought is due to the variations in the climatic conditions and the anthropogenic effects. Due to climate change and inadequate rainfall, the moisture in soil gets affected which reduces the supply of water to the vegetation and also to the groundwater resources. The onset of drought is difficult to predict but it can be monitored with the help of various influential parameters. Suitable drought resilience techniques should be adopted to recover the loss and mitigate the effect of drought in a region. Proper monitoring and management of drought mitigation strategies should be followed to prevent the occurrence of such a kind of disaster. In this study, the authors provided a scientometric analysis and a wide-ranging review on drought indices. The scientometric analysis using VOSviewer showcases the current trend in the research using the most frequently used keywords, most cited articles and authors, and the countries that contributed to the field of drought. A total of 175 articles were identified from various databases and initial screening was done to select the full text articles. The eligible full text articles were selected after excluding the least prominent articles. Finally, 45 articles were included for the final exclusive review process. The review article provides an insight on drought categorization and drought indices derived to determine the severity of drought. The best suited index for drought severity assessment is very hard to identify since it requires more time. The drought indices should be selected in such a manner, that it effectively measures and monitors the severity of drought. A widespread, informative examination of drought indices would benefit the researchers worldwide to reduce their time spent on each article. The aim of this review article is to review the scientific articles regarding drought indices and provide the best solution to derive the drought severity conditions.
Keywords: Scientometric Analysis; VOSviewer; Drought assessment; Drought monitoring; Drought indices